2020
DOI: 10.1101/2020.09.22.308783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico identification and validation of inhibitors of the interaction between neuropilin receptor 1 and SARS-CoV-2 Spike protein

Abstract: Neuropilin-1 (NRP-1) is a multifunctional transmembrane receptor for ligands that affect developmental axonal growth and angiogenesis. In addition to a role in cancer, NRP-1 is a reported entry point for several viruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causal agent of coronavirus disease 2019 (COVID-19). The furin cleavage product of SARS-CoV-2 Spike protein takes advantage of the vascular endothelial growth factor A (VEGF-A) binding site on NRP-1 which accommodates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 79 publications
(163 reference statements)
0
18
0
1
Order By: Relevance
“…As it was mentioned already, the amino acid Asp320 is very important for NRP1 to interact with different ligands and VEGF-A, 29 , 33 as well as for the CendR region in the SARS-CoV-2, 17 , 32 therefore, the region between the amino acids Thr316, Asp320, Ser346, Thr349 and Tyr353 has a very important role for the S1 region of SARS-CoV-2 to interact with NRP1; in this study was carried out a docking directed to amino acids in the b1 region reported in the NRP1 (Thr316, Asp320, Ser346, Thr349 and Tyr353), 17 that is important to interact with the S-Protein (S1 region) of SARS-CoV-2, 16 since it has been shown that by preventing this interaction, the infectious process caused by this virus could be reduced . 14 , 15 , 17 …”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…As it was mentioned already, the amino acid Asp320 is very important for NRP1 to interact with different ligands and VEGF-A, 29 , 33 as well as for the CendR region in the SARS-CoV-2, 17 , 32 therefore, the region between the amino acids Thr316, Asp320, Ser346, Thr349 and Tyr353 has a very important role for the S1 region of SARS-CoV-2 to interact with NRP1; in this study was carried out a docking directed to amino acids in the b1 region reported in the NRP1 (Thr316, Asp320, Ser346, Thr349 and Tyr353), 17 that is important to interact with the S-Protein (S1 region) of SARS-CoV-2, 16 since it has been shown that by preventing this interaction, the infectious process caused by this virus could be reduced . 14 , 15 , 17 …”
Section: Discussionmentioning
confidence: 86%
“…We selected ten compounds depicted here as N1 to N10 from the Express-pick Collection Stock from Chembridge library (ChemBridge Corp.) and the analysis of the interaction of each compound with NRP1 was carried out with the interaction report ( Table 2 and details in Table S1–S11). In addition, it was determined the average interaction for compound EG00229 and EG01377 (with reports of inhibitory effect between NRP1 with VEGF-A 29 , 31 and S-Protein of SARS-CoV-2 32 ), with an average value of −4.95 kcal/mol −1 and −4.86 kcal/mol −1 respectively (interaction details in Tables S1 and S12). Afterwards, the theoretical toxicity for the ten compounds was evaluated with two websites (Prediction of Toxicity and PreADMET web server).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations